Determining of Heating Fans Productivity of the Car Body Automatic Ventilation System - Tryhub, O. A.; Zahubynoha, V. V.; Tarandushka, L. A. (Visnyk of Vinnytsia Politechnical Institute, 2018)
All drivers and passengers are aware of the heating air and car elements in the car’s cabin when it is on the open car park in the summer season. In summertime, when the weather is sunny, the car and its cabin can be heated by more than 30 °С, compared to ambient temperatures. In such temperature modes, transportation of people is not possible, as a person can get a heat stroke, which will result in loss of working capacity or a fatal case. Usually such problems are solved by installing additional climate control systems in the car. To provide the necessary temperature indicators in the car cabin, air conditioning systems are used. However, the most important disadvantage of such systems is that they all work only when the engine is started and absolutely not capable when the car is in the parking lot. While the car is parked, its engine is off and the air conditioning system cannot provide ventilation and maintain a comfortable temperature. To solve this problem, the authors developed an autonomous solar-powered cabin ventilation system independent of the engine. To ensure the effectiveness of such a system, the air coming out of the cabin should not be able to heat up to temperatures not comfortable for humans. This should be ensured by the necessary performance of the fans, which remove the heated air from the cabin. A mathematical model for calculating the performance of inlet fans in the system of automatic cabin ventilation is devised in the article. The shape of the cabin can be of any construction. On the basis of the presented model, the calculations to determine the performance of ventilators were performed for ventilation KUNG type cabin. It has been determined that the performance of the fans depends mainly on the area of the cabin surfaces and the geographical location.